The Delay Factors of Early Breast Cancer Detection Patients in Indonesia - Seni Mariska; Yulius Tiranda; Windy Astuti C.N (Caring: Indonesian Journal of Nursing Science, 2021)
Breast cancer is the number one death caused to women. The higher mortality rate is because the patients are diagnosed at the advanced stage. The cancer patients do not know the signs and symptoms of breast cancer and cannot do a breast self-examination (SADARI) because the cancer education in the community is insufficient. Delaying in detecting breast cancer will delay the treatment. This research aims to explore the delay factors of early breast cancer detection. It used a literature review approach with 4 electronic databases, including Google Scholar, Pubmed, Garuda, and Perpusnas, with published years of 2015-2020. The keywords are delay factors, detection, medical checkup, treatment, and breast cancer. Of 892 identified articles, only 9 articles fulfilled the inclusion criteria. The reviewed articles are the researcher and supervisor's discussion and validation using the Prisma Guideline. The 9 articles show delay factors of detecting breast cancer, including education, knowledge, income, information/mass media, husband/family support, health service center distance, health facilities, treatment cost, alternative treatment, age, pain, and fear. The research concluded that the 12 factors causing the breast cancer patients late in receiving treatment and already in advance stage cancer because they did not do breast cancer detection.